General Exhibit Group (Max Rigot Selling Co)
This group will house exhibits of applied sciences and industries. It will be a continuous structure, with a series of seven pavilions and courts, with a series of seven pavilions and courts, each being similar in mass form, but varying in detail, materials and decorations. Within these individual pavilions will be a flexible arrangement of exhibit space, so that the character of the industry exhibiting will be definitely expressed, whether it be a large or small exhibit.